From lymphatic endothelial cell migration to formation of tubular lymphatic vascular network - Shiiya, Tomohiro; Hirashima, Masanori (Frontiers in Physiology, 2023)
During development, lymphatic endothelial cell (LEC) progenitors differentiate from venous endothelial cells only in limited regions of the body. Thus, LEC migration and subsequent tube formation are essential processes for the development of tubular lymphatic vascular network throughout the body. In this review, we discuss chemotactic factors, LEC-extracellular matrix interactions and planar cell polarity regulating LEC migration and formation of tubular lymphatic vessels. Insights into molecular mechanisms underlying these processes will help in understanding not only physiological lymphatic vascular development but lymphangiogenesis associated with pathological conditions such as tumors and inflammation.